Tatjana Gajić. Paradoxes of Stasis: Literature, Politics, and Thought in Francoist Spain. Lincoln: U of Nebraska P, 2019. - Nicolás Fernández-Medina (Studies in 20th & 21st Century Literature, 2019)
Review of Tatjana Gajić. Paradoxes of Stasis: Literature, Politics, and Thought in Francoist Spain. Lincoln: U of Nebraska P, 2019. 219 pp.
Keywords: Spain; Francisco Franco; Miguel Espinosa; José Luis Arrese; Dionisio Ridruejo; falangismo Jesús Fueyo Álvarez